Evaluation of health referral uptake and linkage to health care after community-based disease screening in urban informal settlement, South Africa - Poopedi, Machuene Ananias (My University, 2019)
Introduction: The present research report paints a picture of a household survey of disease screening in an informal settlement of Diepsloot in Johannesburg, South Africa. Like any other informal settlement or slum in developing and low and middle-income countries (LMICs), the studied population was exposed to various undiagnosed disease conditions due to a lack of access to healthcare services. Study aim: To assess healthcare referral uptake and linkage to healthcare and factors 7 associated with health referral uptake and linkage to healthcare in an informal settlement in Johannesburg. Methods: The baseline study consisted of primary data that was collected from 2000 households and the present study was a prospective cohort of 429 randomly selected participants from the baseline study suspected to have diseases. Data on demographic, mobility, physical activity, mental health, health-seeking behavior, food security and children’s health, women and men’s health was collected. Participants suspected of having 14 disease were given health referral letters to visit the nearest health clinic for medical attention. The participants were further called after days has elapsed to check if they visited the healthcare facility, with an overlap in time for those not found at the required time. Manuscript statistical analysis: Median and interquartile ranges were calculated for continuous variables, frequencies and percentages were calculated for categorical variables. The relationship of health referral uptake, linkage to care and their predictors (socio-demographic status and disease conditions) was assessed by univariate and multivariate Cox 21 proportional hazards regression models. In all associations, statistical significance was considered when the p-value was < 0.05. The time taken for participants to visit the nearest healthcare center was assessed by Kaplan-Meier (KM) survival curve. Results: Of the 429 participants, only 109 (25%) took the referral letter to the clinic and from 109 participants 77 (71%) were linked to care and 32 (29%) not linked to care. The 77 26 participants were linked to care within a period of approximately 3 months (median = 11.4 27 days, inter quartile range (IQR) (1 – 84 days). There were also 240 (56%) participants who 28 failed to visit the clinic and stated health system problems 17 (7%), patient problems 213 (89%) and health worker problems 10(4%) as their barriers to access healthcare and 80 (19%) 30 participants were not reached. The association of health referral uptake and linkage to care with socio-demographic factors and disease conditions were mixed (Hazards Ratio (HA) < 1 or HA > 1), with no statistical significant (p > 0.05). Conclusion: Overall, there was a low uptake of healthcare services (31%) and linkage to healthcare (20%) in Diepsloot. The majority of the participants were lost to follow up with 80 (19%) of the participants not reached and other 240 (56%) participants were reached but failed to visit the healthcare center, hence studies with larger sample sizes are not only suggested but warranted.
A research report submitted to the School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters of Science in Epidemiology October 2019